The FITNESS study: longitudinal geriatric assessment, treatment toxicity, and biospecimen collection to assess functional disability among older adults with lung cancer - Grogan, Madison; Hoyd, Rebecca; Benedict, Jason; Janse, Sarah; Williams, Nyelia; Naughton, Michelle; Burd, Christin E.; Paskett, Electra D.; Rosko, Ashley; Spakowicz, Daniel J.; Presley, Carolyn J. (Frontiers in Aging, 2024)
Introduction: Older adults with chronic disease prioritize functional independence. We aimed to describe the feasibility of capturing functional disability and treatment toxicity among older adults with lung cancer using a longitudinal comprehensive geriatric assessment (CGA) and molecular biomarkers of aging. Methods: This prospective study included adults ≥60 years with any newly diagnosed non-small-cell lung cancer. Participants were recruited from central Ohio (2018-2020). Study assessments included the Cancer and Aging Research Group CGA (CARG-CGA), short physical performance battery (SPPB), and the blessed orientation-memory concentration (BOMC) test at baseline, 3, 6, and 12 months. Activities of daily living (ADLs) and instrumental ADLs (IADLs), quality of life (QoL, PROMIS 10), and treatment toxicity were captured monthly. Stool and blood were collected to characterize the gut microbiome and age-related blood biomarkers. Results: This study enrolled 50 participants with an average age of 71.7 years. Ninety-two percent of participants were Caucasian, 58% were male, and all were non-Hispanic. Most had advanced stage (stage III/IV: 90%; stage I/II: 10%), with adenocarcinoma the predominant histologic subtype (68% vs. 24% squamous). First-line treatments included chemotherapy (44%), immune checkpoint inhibitors (ICIs, 22%), chemotherapy and ICIs (30%), or tyrosine kinase inhibitors (4%). The median baseline CARG toxicity score was 8 (range 2-12). Among patients with treatment-related toxicity (n=49), 39 (79.6%) cases were mild (grade 1-2), and 10 (20.4%) were moderate to severe (≥ grade 3). Treatment toxicity was greater among those with a CARG score ≥8 (28.0% vs. 13.6%). Higher IADL independence, QoL, and SPPB scores at baseline were positively associated with Candidatus Gastranaerophilales bacterium, Lactobacillus rogosae, and Enterobacteria phage P4. Romboutsia ilealis, Streptococcus, and Lachnoclostridium sp An138 and T cell lag3 and cd8a were associated with worse IADLs, QoL, and SPPB scores at baseline. Discussion: A longitudinal CGA and biomarker collection is feasible among older adults undergoing lung cancer treatment. Gut microbe and T cell gene expression changes correlated with subjective and objective functional status assessments. Future research will test causality in these associations to improve outcomes through novel supportive care interventions to prevent functional disability.